AMANDEMEN KE-5: MENUJU KONSTITUSI BARU DI INDONESIA - Nanik Prasetyoningsih (JURNAL ILMIAH HUKUM DAN DINAMIKA MASYARAKAT, 2020)
This paper presents developments in whether or not the 5th amendment needs to be done. The long experience of changing the constitution of the Indonesian state from 1949 to the most recent amendment in 2002, should make important lessons for making further changes to the constitution. Article 37 of the 1945 Constitution opens opportunities for change, but the rigid nature of the constitution and constitutional principles must be the dependent variable of the change itself. The main changes to the 1945 Constitution, the authors present the chronicle differences in the first calling of the changes to the 1945 Constitution which can be used as a consideration for making second calling. The planning of changing the second calling should have been carried out based on an evaluation and study of whether or not the goal of the first calling change was achieved.